BS EN IEC 60794-1-309. Optical fibre cables. Part 1-309. Generic specification. Basic optical cable test procedures. Cable element test methods. Bleeding and evaporation of filling or flooding compounds, Method G9 (11th June 2021) - British Standards Institution,
No abstract available